Аrterial stiffness and cardiovascular autonomic neuropathy relationship in children and adolescents with type 1 diabetes mellitus - Dmitriy Nikitich Laptev (Сахарный диабет)
Aim. To evolve the association between cardiac autonomic function and arterial stiffness in children and adolescents with type 1 diabetes mellitus (T1DM). Materials and methods. 72 T1DM patients aged 7?18 years without history of macrovascular complications or renal disease, including microalbuminuria, were involved in the study. Cardiac function was assessed by the cardiovascular tests and 24-hour ECG monitoring with automatic calculation of QT interval and heart rate variability (HRV) parameters. Artery stiffness was assessed by measurement of pulse wave velocity (PWV) and augmentation index (AI) obtained from arterial blood pressure monitoring for 24 hours. Results. Estimated prevalence of cardiovascular autonomic neuropathy (CAN) was 31,9%. CAN+ patients had significantly higher PWV and AI than those without CAN. A negative correlation between PWV and AI with some cardiovascular tests and HRV parameters was observed. In multivariable analysis, AI was independent predictor of autonomic dysfunction defined as number of positive cardiovascular tests, HRV parameters below normal values and prolongation of QT interval (?. =0,18; p=0,035). Conclusion. Cardiac autonomic function is an independent predictor of arterial stiffness, in children and adolescents with T1D without macrovascular and renal complications. The presence of cardiovascular risk factors and arterial stiffness in children and adolescents with T1DM may contribute to the increased cardiovascular morbidity and mortality in adulthood in patients with CAN.